Evaporation of ice droplet - Ng, Say Chong. (2012)
Sublimation of a substance is the process of transitioning from solid phase to vapor phase. Despite the common occurrence of sublimation, the process is still not predictable up till this date. A theoretical approach based on the transition probability concept of quantum mechanics and Boltzmann deification of entropy, called Statistical Rate Theory (SRT) has been used to investigate the evaporation process of liquids. Previous studies had shown that this model predicted the conditions for evaporation of water and heavy water at spherical and cylindrical interfaces very well. Hence the application of SRT is to extend further to study the sublimation of ice.